An accurate 3D augmented reality navigation system with enhanced autostereoscopic display for oral and maxillofacial surgery. Issue 4 (15th April 2022) - Han, Boxuan; Li, Ruiyang; Huang, Tianqi; Ma, Longfei; Liang, Hanying; Zhang, Xinran; Liao, Hongen
Abstract: Background: Oral and maxillofacial surgery demands high precision navigation to achieve optimal surgical outcomes. Augmented reality (AR) has been a promising solution for intuitive and accurate guidance, whereas existing systems have room for improvement. Methods: We propose a high quality and accurate in situ AR navigation system. Enhanced image quality is achieved by deploying eye tracking in lenticular‐based autostereoscopic display. Viewpoint tracking and optical tracking are integrated to assure accurate in situ images. Results: The proposed system can provide in situ AR images in real‐time, with a viewing angle of 59.5° × 49.1°, 3D image resolution of 0.35 × 0.21 mm, and image accuracy of 0.99 ± 0.70 mm. A maxillary drilling experiment obtains average position error of 1.12 ± 0.30 mm and localization time of 8.7 ± 3.9 s, significantly better than conventional 2D navigation system. Conclusions: The proposed system can display high‐quality AR images and therefore reduce positioning error and operating time.